2019
DOI: 10.7150/thno.30268
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multimodal NIR-II Nanoprobe for the Detection of Metastatic Lymph Nodes and Targeting Chemo-Photothermal Therapy in Oral Squamous Cell Carcinoma

Abstract: Current surgical treatment for oral squamous cell carcinoma (OSCC) must be as precise as possible to fully resect tumors and preserve functional tissues. Thus, it is urgent to develop efficient fluorescent probes to clearly identify tumor delineation, as well as metastatic lymph nodes. Chemo-photothermal therapy combination attracted a growing attention to increase anti-tumor effect in various types of cancer, including OSCC. In the present study, we designed a multimodal NIR-II probe that involves combining p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 65 publications
1
62
0
1
Order By: Relevance
“…A multifunctional NP termed HT@CDDP was capable as a theranostic agent for oral squamous cell carcinoma. HT@CDDP provided sufficient tumor contrast up to 24 hr after injection while also suppressing tumor growth with combinatorial chemo‐PTT (Wang et al, ).…”
Section: Nanoparticle Strategies For Image‐guided Surgerymentioning
confidence: 99%
“…A multifunctional NP termed HT@CDDP was capable as a theranostic agent for oral squamous cell carcinoma. HT@CDDP provided sufficient tumor contrast up to 24 hr after injection while also suppressing tumor growth with combinatorial chemo‐PTT (Wang et al, ).…”
Section: Nanoparticle Strategies For Image‐guided Surgerymentioning
confidence: 99%
“…33 Photothermal stability is another important parameter for evaluating the photothermal agents. 3,53 The MNPH2 solution was exposed to an 808 Figure 3D. The time constant for heat transfer of the MNPH2 was calculated to be 243 s. (F) Photothermal stability of MNPH2 (100 μg/mL) in DI water upon irradiation for six cycles (808 nm, 0.5 W/cm 2 ).…”
Section: Photothermal Performance Of Mnph2mentioning
confidence: 99%
“…A novel fluorescence imaging approach in the second NIR window (NIR-II, 1000-1700 nm) provides deeper tissue penetration (~10 mm), a higher signal-tonoise ratio, and better spatial resolution than NIR-I because of minimal photon scattering and tissue autofluorescence. 2 Recent studies, including those regarding the detection of metastatic lymph nodes, 3 tumor and vessel imaging, [4][5][6] and intraoperative guidance, 7,8 have shown that biological imaging advantages significantly improves as wavelengths increase. Thus far, quantum dots, [9][10][11] carbon nanotubes, 12,13 rare earth-doped nanoparticles, 14,15 squaraine dyes, 16,17 semiconducting polymer nanoparticles, 18 and small-molecule dyes 5,19,20 have all been actively used for NIR-II imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present research in the field of nanomedicine for OSCC treatment is mostly focused on PTT with chemotherapy. 30,31 Statistical data have shown that, over the past 40 years, the application of cytotoxic chemotherapeutic drugs has not significantly ameliorated the survival or life quality of patients with oral cancer. 32,33 Therefore, exploring new synergistic therapeutic modalities to achieve safe and effective treatment for OSCC, as well as to ameliorate the prognosis, is highly urgent and necessary.…”
Section: Introductionmentioning
confidence: 99%